Biophysical Insights into Cancer Transformation and Treatment. (11th June 2013) - Pokorný, Jiří; Foletti, Alberto; Kobilková, Jitka; Jandová, Anna; Vrba, Jan; Vrba, Jan; Nedbalová, Martina; Čoček, Aleš; Danani, Andrea; Tuszyński, Jack A.
Abstract : Biological systems are hierarchically self-organized complex structures characterized by nonlinear interactions. Biochemical energy is transformed into work of physical forces required for various biological functions. We postulate that energy transduction depends on endogenous electrodynamic fields generated by microtubules. Microtubules and mitochondria colocalize in cells with microtubules providing tracks for mitochondrial movement. Besides energy transformation, mitochondria form a spatially distributed proton charge layer and a resultant strong static electric field, which causes water ordering in the surrounding cytosol. These effects create conditions for generation of coherent electrodynamic field. The metabolic energy transduction pathways are strongly affected in cancers. Mitochondrial dysfunction in cancer cells (Warburg effect) or in fibroblasts associated with cancer cells (reverse Warburg effect) results in decreased or increased power of the generated electromagnetic field, respectively, and shifted and rebuilt frequency spectra. Disturbed electrodynamic interaction forces between cancer and healthy cells may favor local invasion and metastasis. A therapeutic strategy of targeting dysfunctional mitochondria for restoration of their physiological functions makes it possible to switch on the natural apoptotic pathway blocked in cancer transformed cells. Experience with dichloroacetate in cancer treatment and reestablishment of the healthy state may help in the development of novel effective drugs aimed at the mitochondrial function.